The Role of Family Welfare Empowerment Cadre on Stunting Reduction in Ende Sub-District - Sama, Gratiana; Kara, Yuliana Maria D'Karmel; Separ, Fransiskus Maria (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Stunting is still one of the nutritional problems that occur in Indonesia, characterised by physical stunting. Children with developmental delays are more susceptible to diseases that can affect their level of intelligence. Developmental delays can be overcome by starting with pre-pregnancy preparation for adolescents, brides-to-be, followed by pregnant women, breastfeeding mothers and young children. Community empowerment is a key strategy in stunting reduction programs. The role of family assistance by family planning cadres, midwives and FWE cadres is important through counselling activities, referral service facilities, social assistance facilities for families at risk of stunting and surveillance of target groups at the village level. The approach to implementing this program is made with a service Learning Program Approach System. The training method in the mini workshop used was to facilitate and educate FWE cadres about the role of the FWE Team in the process of accelerating stunting reduction in the Ende District area, Ende Regency, East Nusa Tenggara Province. The population in this activity was 10 FWE cadres consisting of representatives of FWE cadres from all of Ende District. This activity was carried out in the office environment of the Ende District Family Planning Extension Office on 27 June 2023. It can be concluded that the support and cooperation from the FWE team is still lacking due to the lack of knowledge about the role and duties of the family welfare cadre as a family companion. Therefore, it is hoped that through deepening knowledge and empowerment motivation, the role of family welfare activist cadres will be able to collaborate and synergize with family planning extension cadres and midwives more optimally for the realization of reducing stunting rates in Ende District, more specifically in the 9 affected villages.